Implementasi Sistem Arsip Keuangan Berbasis Google Sites sebagai Inovasi Digitalisasi Administrasi pada Balai Pengawas Obat dan Makanan (BPOM) di Jambi - Ahmad Nasukha; Nisa Rifka Azizah; Syahril Agustin; Rangga Wardana (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Effective digital archive management is a key factor in supporting the administrative efficiency of government agencies. Balai Pengawas Obat dan Makanan (BPOM) di Jambi, as a regional technical implementation unit of the National Agency of Drug and Food Control, faces operational challenges related to financial document retrieval that relies on manual, non-centralized processes. This research aims to implement a financial archive system based on Google Sites as an innovation in digitizing administrative management at BPOM di Jambi. The research employed a descriptive method with an implementation approach, encompassing observation, system design, development, functional testing using the black-box testing method, and evaluation. The results indicate that the Google Sites-based financial archive system successfully provides centralized navigation menus for various financial document categories, including Uang Persediaan (UP), Langsung (LS), Bendahara Pengeluaran (BP), SPP, SPM, SP2D, and SK Tim Keuangan, all integrated directly with structured Google Drive folders. Black-box testing confirmed that all navigational features functioned without errors. The implementation of this system significantly accelerated the financial document retrieval process compared to conventional methods, reduced dependence on manual administration, and improved transparency of financial information within the organization. This study demonstrates that no-code platforms such as Google Sites can serve as an effective and low-cost solution for digital transformation of administrative management in government agencies at the regional level.